2011
DOI: 10.1007/s00221-011-2931-5
|View full text |Cite
|
Sign up to set email alerts
|

Touch perception throughout working life: effects of age and expertise

Abstract: Fine motor skills including precise tactile and haptic perception are essential to the manipulation of objects. With increasing age, one's perception decreases; however, little is known about the state of touch perception in middle-aged adults. This study investigated the extent to which the decline in touch perception affects adults throughout their working life. In addition, the influence of work-related expertise on tactile and haptic perception was examined in an attempt to determine whether expertise, in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

3
55
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
4
3
2

Relationship

1
8

Authors

Journals

citations
Cited by 68 publications
(61 citation statements)
references
References 63 publications
3
55
0
Order By: Relevance
“…27,29 Consistent with previous findings, we showed that spatial acuity measured by the grating orientation test declines with age-at least for "healthy" fingers. 30 This trend could not be shown for the injured side. A neural mechanism explaining why age is associated with the grating orientation test only on the healthy side might be the age-related reduction in peripheral innervation density.…”
Section: Discussionmentioning
confidence: 88%
“…27,29 Consistent with previous findings, we showed that spatial acuity measured by the grating orientation test declines with age-at least for "healthy" fingers. 30 This trend could not be shown for the injured side. A neural mechanism explaining why age is associated with the grating orientation test only on the healthy side might be the age-related reduction in peripheral innervation density.…”
Section: Discussionmentioning
confidence: 88%
“…It has also been suggested that work-related expertise in fine dexterous manipulation does not attenuate age-related changes in cutaneous sensation at the fingertip (Reuter et al 2012). Rather, changes in cutaneous thresholds on the palm may have implications for changes in motor control, especially for tasks involving the whole hand, rather than just the fingers, e.g., power grip versus precision grip.…”
Section: Functional Implicationsmentioning
confidence: 99%
“…This allows, for instance, to prevent an object from slipping when moving or holding it. Although the dexterous use of hands is impaired with age (for an overview, see Diermayr, McIsaac, & Gordon, 2010) from middle adulthood onward (Lindberg, Ody, Feydy, & Maier, 2009;Reuter, Voelcker-Rehage, Vieluf, & Godde, 2012;, it has been shown that older adults can improve performance or acquire new tasks (Voelcker-Rehage, 2008). So far, agerelated changes in fine motor control and learning have mainly been investigated in unimanual force modulation tasks.…”
mentioning
confidence: 98%